Public Policies: the importance of effective applicability for early detection of congenital heart disease (Research, Society and Development, 2021)
Introduction: Malformations in the heart and vessels are derived from errors in cardiac development and evolution during pregnancy and persist after birth. These events characterize congenital heart disease (CC). Neonatal Screening is essential for the prevention, promotion, and health recovery of newborns. Objective: assess whether public policies implemented effectively interfere in the early detection of congenital heart disease. Methods: FAMERP Research and Ethics Committee approved the study. We conducted a cross-sectional study with a descriptive design and quantitative-analytical approach in a reference hospital in the inland of São Paulo State. We formulated a four-part questionnaire with characterization, data regarding prenatal care; diagnosis; knowledge of family members. Inclusion criteria: parents who volunteered to participate in the research. Exclusion criteria: parents not found to answer the questionnaire. Results: predominantly female sample, married, residing in the Southeast Region, aged up to 30 years, one child, completed high school, and a family income of one minimum wage. We noticed that 43.14% of pregnant women attended six or more prenatal consultations, as recommended. In 60.78% of neonates with CC, the diagnosis took place only after birth. There are reports from mothers about not having a multidisciplinary team during prenatal care. Conclusion: with trained health professionals and the work of the multidisciplinary team, it is possible to notice signs suggestive of CC, promote qualified care, and detect CC early. It is possible to start the treatment at the origin service or forward it, Considering the material and human resources, even under the home treatment resource (TFD), recommended by the Ministry of Health.